Nanobiosensing with graphene and carbon quantum dots: Recent advances - Walther, Brandon K.; Dinu, Cerasela Zoica; Guldi, Dirk Michael; Sergeyev, Vladimir G.; Creager, Stephen E.; Cooke, John P.; Guiseppi-Elie, Anthony (Materials Today, 2020)
Graphene and carbon quantum dots (GQDs and CQDs) are relatively new nanomaterials that have demonstrated impact in multiple different fields thanks to their unique quantum properties and excellent biocompatibility. Biosensing, analyte detection and monitoring wherein a key feature is coupled molecular recognition and signal transduction, is one such field that is being greatly advanced by the use of GQDs and CQDs. In this review, recent progress on the development of biotransducers and biosensors enabled by the creative use of GQDs and CQDs is reviewed, with special emphasis on how these materials specifically interface with biomolecules to improve overall analyte detection. This review also introduces nano-enabled biotransducers and different biosensing configurations and strategies, as well as highlights key properties of GQDs and CQDs that are pertinent to functional biotransducer design. Following relevant introductory material, the literature is surveyed with emphasis on work performed over the last 5 years. General comments and suggestions to advance the direction and potential of the field are included throughout the review. The strategic purpose is to inspire and guide future investigations into biosensor design for quality and safety, as well as serve as a primer for developing GQD- and CQD-based biosensors.
CRIS-Team Scopus Importer:2020-05-22